Rancang Bangun Alat Pembersih Telur Asin Otomatis Berbasis Arduino Uno Untuk UMKM Di Kota Malang - Nugrahanto, Indrawan; Sungkono, Sungkono; Arisandi, Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2022)
a lot, almost 90% is on the Micro, Small and Medium Enterprises (MSME) scale. At the time of carrying out the mechanism of the salted egg cleaning process the majority still use the manual method and of course this takes quite a long time and is inefficiency of human labor. To overcome this problem, the author designed an automatic cleaning tool in order to speed up the manufacture of salted eggs, especially in the egg cleaning process. The system of this tool includes an Arduino Uno microcontroller module, a BTS7960 motor driver module, a two-channel relay module, a DC motor, a proximity sensor, a 16x2 LCD, a buzzer, an on/off switch, and a push button. With the initial step of entering the dirty egg then the egg will roll down through the egg brush, with a certain time that we have set up then the egg will go down into a special container for the second cleaning process, so that from the dirty egg due to the diffusion process, it will turn into a clean egg and ready to be sale in market. So that by using this tool we have an effective of time and labor efficiency.